In vivo lineage tracing reveals Axin2-expressing, long-lived cortical thymic epithelial progenitors in the postnatal thymus. - Si Hui Tan; Roel Nusse (PLoS ONE)
In the thymus, cortical and medullary thymic epithelial cells (TECs) are instrumental for generating a repertoire of functional T cells. Hence, there has been much interest in the ontogeny of TECs. While medullary TEC (mTEC) and bipotent progenitors have been identified, the existence of a cortical TEC (cTEC) progenitor remains ambiguous. In this study, we used lineage tracing based on a target gene of the Wnt pathway, Axin2. We found that Axin2 initially labels cells in both the cortical and medullary compartments. Using Axin2-CreERT2 mice to track the fate of labelled cells, we identified long-lived cortical TEC progenitors that give rise to expanding clones and contribute to homeostasis in postnatal thymus. In contrast, no clonal expansion was found in the medullary or in the K5K8-double positive compartments. The identification of cTEC progenitors and their regulation by Wnt signaling have important implications for our understanding of thymus physiology during homeostasis and TEC-related disorders.